A single chart with supplementary runs rules for monitoring the mean vector and the covariance matrix of multivariate processes - Costa, Antônio F. B. [UNESP]; Machado, Marcela A. G. [UNESP] (Elsevier, 2013)
The MRMAX chart is a single chart based on the standardized sample means and sample ranges for monitoring the mean vector and the covariance matrix of multivariate processes. User's familiarity with the computation of these statistics is a point in favor of the MRMAX chart. As a single chart, the recently proposed MRMAX chart is very appropriate for supplementary runs rules. In this article, we compare the supplemented MRMAX chart and the synthetic MRMAX chart with the standard MRMAX chart. The supplementary and the synthetic runs rules enhance the performance of the MRMAX chart. © 2013 Elsevier Ltd.
Keywords: Control charts; Covariance matrix; Mean vector; Multivariate processes; Supplementary runs rules